Investigation of Near-Fundamental-Frequency Oscillation in a Renewable Power Integrated System with MMC-HVDC Transmissions - Tian, Xiaoyu; Dong, Wenkai; Zhai, Wenhui; Yang, Guixing; Kang, Pengpeng; Xie, Xiaorong (2024 IEEE 8th Conference on Energy Internet and Energy System Integration (EI2), 2024)
Near-fundamental-frequency oscillations (NFFOs) have been observed in practical renewable power integrated system via MMC-HVDC, of which the mechanism is not fully revealed yet. Therefore, in this paper, potential dominant influencing factors of the NFFO are explored based on a general renewable power integrated system at first. Then the equivalent circuit model of the system is built. By calculating the total resistance, the physical mechanism of the NFFO is revealed.